GOALS AND FUNCTIONS OF CONTROL AND SUPERVISION OF FORESTRY MANAGEMENT IN UKRAINE (Bulletin of criminological association of Ukraine, 2025)
It is substantiated that the tasks of supervision and control over forestry management in Ukraine are most expedient to be divided into two groups: general and special. It is argued that the following are most expedient to include in the general tasks: ensuring the legality of the functioning of the relevant sphere of public life; checking the rational use of resources, primarily forest, as well as other financial and material and technical instruments and means used in the implementation of relevant activities; identifying and preventing offenses, as well as establishing the conditions and factors that determine their occurrence; ensuring the implementation of measures aimed at preventing offenses; assessing the effectiveness of forestry management; ensuring the fulfillment of the rights and obligations of forest users. It is substantiated that the following are special tasks: identifying violations of the boundaries of allocated areas, illegal timber export, use of forests without permits; monitoring the qualitative and quantitative state of forests, including their biodiversity; assessment of the legality of the use of forest resources, which includes the analysis of permits, quotas, temporary use agreements; prevention of degradation of forest ecosystems; assessment of the timeliness, completeness, compliance of the species composition and quality of restoration of felled forests. It is emphasized that functions characterize the external manifestation of the practical activity of subjects that implement the tasks of supervision and control in the studied sphere of social life. Their list includes: protective; law enforcement; preventive; informational; educational.
Keywords: supervision; control; forestry; tasks; functions